Predictive factors for intraoperative excessive bleeding in multinodular goitre with or without hyperthyroidism - Sagar, Ramesh C.; Ravikumara, Gudekote; Malipatil, V. B. (International Surgery Journal, 2018)
Background: Multinodular goitre disease frequently results in and is the most common cause of hyperthyroidism. It also often results in an enlarged thyroid. It also known as toxic diffuse goiter, is an autoimmune disease that affects the thyroid. This study evaluates all the factors that cause intra-operative blood loss and how it affects the Grave’s disease. Methods: This study was conducted in Raichur Institute of Medical Sciences Raichur on 200 patients with multinodular goitre disease, who underwent thyroidectomy during the period between November 2010 to July 2015. Results: The majority of patients were females which constitute about 76.3% with a median age of 33 years. The median period between the onset of the disease and operation was 15 months. Weight of thyroid in grams was 40. Post-operative hospital stay was 4 hours. Univariate analysis revealed that the strongest correlation of AIOBL was noted with the weight of thyroid (p <0.001). Additionally, AIOBL was correlated positively with the period between disease onset and surgery (p <0.001) and negatively with preoperative free T4 (p <0.01). Occurrences of postoperative complications, such as recurrent laryngeal nerve palsy or hypoparathyroidism, and postoperative hospital stay were not correlated with AIOBL. Conclusions: For multinodular goitre, for excessive bleeding during surgery, a large goiter presented as a predictive factor, and transfusion of blood should be considered in cases in which goitre weighs more than 200 g.